Wealth effect of UK acquirers from cross-border and national M&As announcement in 1996-2015 - Chen, Li-Ming (2016)
As the most important means of foreign direct investment, mergers and acquisitions involve considerable funding in international deals. Cross-border transactions have experienced a remarkable growth in the last decades. This study aims to examine the shareholder wealth effect from different factors distinguish national and cross-border acquisitions. The sample is 357 successful transactions across all industries (except finance) during 1996 -2015, where all the acquirers are UK public companies.